Application of the Six Functionals Fixed Point Theorem: Positivity for RL-type Nonlinear FBVPs with p-Laplacian - Krushna, Boddu Muralee Bala; Prasad, Kapula Rajendra (Discontinuity, Nonlinearity, and Complexity, 2026)
We study a coupled system of RL–type nonlinear fractional-order boundary value problems with a p-Laplacian operator in this paper. Using two Kernels, the considered coupled system can be transformed into an integral system. Due to the increased applicability of SFFPT to non-linear problems, sufficient conditions for the existence of positive solutions to the proposed problem are derived. Our technique for accomplishing these results is straightforward, but its application in the current context problem is new.